(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Network-based access to information or communication tools such as email and calendars is made possible by cloud computing. In terms of communication, Whatsapp is also a cloud-based infrastructure and is a prime example of cloud computing. All communication or data is housed in the service provider’s hardware. Businesses of all sizes, types and industries employ a wide range of use cases, such as data backup, email, disaster recovery, software development, virtual desktops, testing, big data analytics, as well as consumer-facing online apps. A health care system built on the cloud reduces operating costs while providing more personalized treatment, effective procedures, and better health services. Patients have increased access to their medical records and receive instant answers from healthcare professionals. In this paper, the author discusses cloud computing, and how cloud computing is beneficial to the health industry. The main purpose of this paper is to know more about cloud computing’s impact healthcare industry. In the future through this paper, will be aware of the benefits of cloud computing for the health industry.